Pengembangan LKPD Tematik pada Tema 4 Subtema 1 Pembelajaran 1 di Kelas V SDN 36 Pontianak Kota - Haliza Rizki; Hery Kresnadi; Suparjan Suparjan; Kartono Kartono; Asmayani Salimi (FONDATIA, 2023)
This study aims to produce thematic LKPD products that are valid and practical to use. This research uses a Research and Development (R&D) approach with the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The data sources in this study were 27 students in class V at SDN 36 Pontianak City. Data collection techniques in this study were interviews, questionnaires and documentation. The product validity research results of thematic LKPD obtained the "Very Valid" category. That is, on the material aspect, an average score of 4.74, was obtained, on the design aspect, an average score of 4.89, on the language aspect, an average score of 4.81 was obtained in the trial activities. The results of practicality research on thematic LKPD products obtained an average value of 4.74 in the trial activities with the criteria of "Very Practical". Based on the results of the Thematic LKPD product trials, it was declared very valid and very practical to use in the learning process.